Analisis Tindak Tutur Ilokusi pada Teks Drama dalam Buku Bahasa Indonesia Kelas VIII Kurikulum 2013 - Dian Nugraheni; Ulfi Akhyatussyifa; Vianni Nifattien Vrisna Putri; Putri Dzakiyyatul Khotimah; Nida Rufaida; Asep Purwo Yudi Utomo; Zulfa Fahmy (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article examines drama texts that focus on pragmatic aspects, namely illocutionary speech acts. The texts studied are drama texts listed in the Indonesian Language Book Class VIII Curriculum 2013. The background of this article is based on the diversity of the application of illocutionary speech acts in the drama text. The purpose of this article is to analyze illocutionary speech acts in drama texts. The method used in this research uses a methodological approach, namely descriptive qualitative, and a theoretical approach, namely pragmatics. The data of this article consists of a group of sentences that form a paragraph taken from the drama text in the Indonesian Language Book Class VIII Curriculum 2013 and studied commensurate with the classification of illocutionary speech acts. The data source comes from the drama text in the Indonesian Language Book Class VIII Curriculum 2013. The techniques used are note-taking techniques and listening techniques or reading data which are data collection techniques. The data analysis technique in the research uses agih and padan techniques. Data presentation techniques with informal techniques. From the existing data, the conclusion is that there are several forms of speech acts in the drama text, namely: representative/assertive, expressive, commissive, directive, and declarative illocutionary speech acts contained in the drama text. This article has benefits for students because it can provide knowledge about the classification of illocutionary speech acts.